2020
DOI: 10.1016/j.ijid.2020.09.1466
|View full text |Cite
|
Sign up to set email alerts
|

COX2 inhibition in the treatment of COVID-19: Review of literature to propose repositioning of celecoxib for randomized controlled studies

Abstract: Highlights Coronavirus triggered pulmonary and systemic disease has an unpredictable clinical course in different subsets of patients led us to go through literature in a hope that we might contribute to this worldwide fight. COX2, p38 MAPK, IL-1b, IL-6 and TGF-b are playing pivotal roles in coronavirus related cell death, cytokine storm and pulmonary interstitial fibrosis. Still ongoing discussions on refining immunomodulation in COVID-19 without COX2 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 37 publications
1
44
0
2
Order By: Relevance
“…Indeed, chronic low-grade inflammation has a negative impact on host immunity, as elevated inflammatory responses are detrimental for vaccine efficacy against influenza [ 33 ] or yellow fever [ 34 ]. In this context, clinically approved drugs with immunomodulatory properties such as metformin, imiquimod [ 35 ] and anti-inflammatory drugs (e.g., aspirin and NSAIDS) may represent attractive approaches to increase efficacy of vaccines by transiently alleviating chronic low-grade inflammation prior to vaccination [ 36 , 37 ]. Further, inflammaging may have multiple health consequences by fueling age-associated diseases including metabolic syndrome, cardiovascular disease, sarcopenia, cancer, and neurodegenerative diseases as most if not all age-related disorders share an inflammatory signature.…”
Section: General Hallmarks Of Immune Agingmentioning
confidence: 99%
“…Indeed, chronic low-grade inflammation has a negative impact on host immunity, as elevated inflammatory responses are detrimental for vaccine efficacy against influenza [ 33 ] or yellow fever [ 34 ]. In this context, clinically approved drugs with immunomodulatory properties such as metformin, imiquimod [ 35 ] and anti-inflammatory drugs (e.g., aspirin and NSAIDS) may represent attractive approaches to increase efficacy of vaccines by transiently alleviating chronic low-grade inflammation prior to vaccination [ 36 , 37 ]. Further, inflammaging may have multiple health consequences by fueling age-associated diseases including metabolic syndrome, cardiovascular disease, sarcopenia, cancer, and neurodegenerative diseases as most if not all age-related disorders share an inflammatory signature.…”
Section: General Hallmarks Of Immune Agingmentioning
confidence: 99%
“…Therefore, it is essential to define the clinical conditions of each patient with COVID-19 and identify the most appropriate treatment for each disease stage based on laboratory data essential to define the evolution of the infection [7,9,22,23]. In patients where the presence of few symptoms is prevalent (pauci-symptomatic subjects), the use of paracetamol, aspirin, and other cyclooxygenase-2 (COX2) inhibitors, appears to be more appropriate [159]. The role of aspirin is being investigated in patients with COVID-19 in RECOVERY trial [160].…”
Section: Covid Treatment Strategy Based On Pathogenetic Mechanismsmentioning
confidence: 99%
“…However, it was demonstrated that resveratrol, through upregulation of Sirt1 activity in rheumatoid arthritis synovial fibroblasts, suppressed the bradykinin-induced COX-2/PGE2 production ( 85 ). SARS-Cov-2 infection causes local and systemic inflammation mediated also by COX-2 eicosanoid products with metabolic dysfunction and tissue damage ( 86 ) Therefore, the resveratrol-induced inhibition of bradykinin-induced COX-2/PGE2 production might be a valuable adjunct anti-inflammatory activity in Covid-19 ( 87 ).…”
Section: Resveratrol Activities On Pathogenetic Mechanisms Involved Imentioning
confidence: 99%
“…Amongst aerosolized suspensions, a nasal spray containing carboxymethylated (1,3/1,6)-β-D-glucan (CM-glucan) combined with resveratrol has been produced and is commercially available for clinical use ( 90 ). β-glucans are high molecular weight polysaccharides acting as “biological response modifiers”, as they can stimulate the immune system exerting anti-viral activities ( 87 ). The combination with CM-glucan greatly improves resveratrol stability in aqueous solutions and, acting in synergy, enhances its biological activities ( 90 ).…”
Section: Resveratrol Pharmacokinetics and Bioavailabilitymentioning
confidence: 99%